2014
DOI: 10.1007/s11046-014-9740-x
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Mycosis in Medical Intensive Care Unit Patients with Severe Alcoholic Hepatitis

Abstract: Patients with severe AH have an increased susceptibility to invasive mycosis associated with high mortality. A high level of suspicion of invasive mycosis in AH patients and prophylactic strategies are needed in those patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 10 publications
2
46
0
Order By: Relevance
“…Lin et al also demonstrated high mortality (66%) in patients with IFI as compared to no‐IFI (14%) in patients with ACLF. Similarly, others had also reported high mortality (57%‐70%) because of fungal infections in patients with cirrhosis . The reasons of such a high mortality include delayed diagnosis, lack of empirical or adequately dosed antifungals, multiple organ failures and poor liver functions in patients with IFI.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Lin et al also demonstrated high mortality (66%) in patients with IFI as compared to no‐IFI (14%) in patients with ACLF. Similarly, others had also reported high mortality (57%‐70%) because of fungal infections in patients with cirrhosis . The reasons of such a high mortality include delayed diagnosis, lack of empirical or adequately dosed antifungals, multiple organ failures and poor liver functions in patients with IFI.…”
Section: Discussionmentioning
confidence: 93%
“…The presence of IFI was suspected and diagnosed based on the Modified European Organization for Research and Treatment of Cancer/Mycoses Study Group (EORTC/MSG) diagnostic criteria (Figure ). The criteria were adapted from and based on previous studies . The criteria were divided into host, clinical and mycological criteria.…”
Section: Methodsmentioning
confidence: 99%
“…Mechanical ventilation, instrumentation, hemodialysis, and number of antibiotics used were some of the risk factors identified in the study. 66 In another recent retrospective review of 185 patients by Alexopoulou and colleagues, 67 prevalence of fungal infections was 6% and 1-month mortality close to 90%. Fungal infections are difficult to diagnose in peritoneal fluid analysis, are usually fatal, and require a high index of suspicion.…”
Section: Importance Of Fungal Infectionsmentioning
confidence: 97%
“…We would like to add that fungal infections may be one of the causes of treatment failure in cirrhotic patients. Fungal infections have mainly been described in cirrhotic patients hospitalised in intensive care units [2] and in those with alcoholic hepatitis [3]. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 (Table).…”
Section: Sirmentioning
confidence: 99%